In-situ graded aluminum nitride powder and preparation method and application thereof

The preparation of aluminum nitride powder by self-combustion-nitriding method solves the problems of easy agglomeration of raw materials and high nitriding temperature in the preparation of aluminum nitride powder, and realizes in-situ grading and high thermal conductivity aluminum nitride ceramic substrates , significantly improves the quality and efficiency of heat dissipation materials.

CN118878335BActive Publication Date: 2025-01-07GANZHOU NONFERROUS METALLURGICAL RES INST
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411354831.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-07
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The existing aluminum nitride powder preparation methods have problems such as easy agglomeration of raw materials, difficulty in mixing uniformly, and high nitriding temperature, which affects the thermal conductivity and the quality of heat dissipation materials.

Method used

By using the self-combustion-nitriding method, the aluminum source, carbon source, oxidant and reducing agent are dispersed into a polar solvent to form a precursor suspension, and after spray drying, nitriding is performed under a nitrogen-containing atmosphere, using the oxidant and reducing agent. The self-combustion reaction reduces the nitriding temperature and decarbonizes under an oxidative atmosphere to prepare in-situ graded aluminum nitride powder.

Benefits of technology

The preparation of in-situ grade aluminum nitride powder at lower temperatures is achieved, which improves the conversion rate and thermal conductivity of the aluminum source, shortens the reaction time, reduces energy consumption, and forms a tighter thermal conductivity path after sintering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of ceramic materials, and specifically to an in-situ graded aluminum nitride powder, and a preparation method and application thereof. The preparation method of the present invention comprises: dispersing an aluminum source, a carbon source, an oxidant and a reducing agent in a polar solvent to obtain a precursor suspension; the oxidant is anhydrous aluminum nitrate and a non-aluminum nitrate, or a hydrate of aluminum nitrate and a non-aluminum nitrate; the reducing agent is urea; spray drying the precursor suspension to obtain a precursor powder; heat treating the precursor powder to cause the precursor powder to undergo a self-combustion reaction to obtain a heat-treated powder; nitriding the heat-treated powder in a nitrogen-containing atmosphere to obtain a nitrided powder; decarburizing the nitrided powder in an oxidizing atmosphere to obtain an in-situ graded aluminum nitride powder. The preparation method provided by the present invention can prepare in-situ graded aluminum nitride powder at a relatively low temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic materials, and in particular to an in-situ graded aluminum nitride powder and a preparation method and application thereof. Background Art

[0002] With the rapid development of microelectronics technology, electronic components are developing towards high performance, miniaturization and micro-miniaturization. The continuous improvement of circuit integration is inevitably accompanied by an increase in unit heat output, which puts higher requirements on the performance of heat dissipation devices. At present, heat dissipation has become an important bottleneck restricting the further improvement of the performance of electronic components. Aluminum nitride has high thermal conductivity (theoretical thermal conductivity can reach 320 W·m -1 ·K -1 ), good insulation, low dielectric constant and dielectric loss, and thermal expansion coefficient close to that of silicon. It is an excellent structural functional material and has been widely used in the fields of electronic information, aerospace, national defense, and chemical materials. Aluminum nitride ceramic substrates processed from aluminum nitride powder are an ideal heat dissipation material for integrated circuits and high-power semiconductor devices. Aluminum nitride powder with good performance is the basis for preparing high-quality aluminum nitride ceramic substrates.

[0003] At present, the preparation methods of aluminum nitride powder include direct nitridation, carbon thermal reduction and mechanochemical methods. The more mature one in industry is the carbon thermal reduction method. The traditional carbon thermal reduction method uses aluminum oxide and carbon black as raw materials, mixes the raw materials by mechanical methods such as ball milling, and prepares aluminum nitride powder through nitridation (temperature reaches 1700~1800 ℃) and decarburization. However, this method has the defects of easy agglomeration of raw materials, difficult to mix evenly, and high nitridation temperature. In addition, good thermal conductivity is one of the important performance indicators of high-quality aluminum nitride substrates. This requires that when sintering the substrate, the aluminum nitride powder should be stacked as closely as possible so as to obtain a good thermal conduction channel after sintering. Therefore, it is of great significance to develop a new aluminum nitride powder preparation process and its application in the preparation of aluminum nitride ceramic substrates in response to the above problems and requirements. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention provides an in-situ graded aluminum nitride powder and a preparation method and application thereof. The preparation method provided by the present invention can prepare in-situ graded aluminum nitride powder at a relatively low temperature.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing in-situ graded aluminum nitride powder, comprising the following steps:

[0007] dispersing an aluminum source, a carbon source, an oxidant and a reductant in a polar solvent to obtain a precursor suspension;

[0008] The oxidizing agent is anhydrous aluminum nitrate and non-aluminum nitrate, or a hydrate of aluminum nitrate and non-aluminum nitrate; the reducing agent is urea;

[0009] spray drying the precursor suspension to obtain a precursor powder;

[0010] The precursor powder is subjected to heat treatment to cause the precursor powder to undergo a self-combustion reaction to obtain a heat-treated powder;

[0011] nitriding the heat-treated powder in a nitrogen-containing atmosphere to obtain a nitrided powder;

[0012] The nitrided powder is decarburized in an oxidizing atmosphere to obtain in-situ graded aluminum nitride powder.

[0013] Preferably, the polar solvent comprises water and / or ethanol.

[0014] Preferably, the aluminum source is at least one of aluminum oxide, aluminum hydroxide and boehmite;

[0015] The carbon source is at least one of carbon black, glucose, sucrose, starch, cellulose, chitosan and chitin.

[0016] The molar ratio of the carbon element in the carbon source to the aluminum element in the aluminum source is 1.5-10:1.

[0017] Preferably, the non-aluminum nitrate comprises at least one of yttrium nitrate, strontium nitrate, cerium nitrate, copper nitrate, samarium nitrate, a hydrate of yttrium nitrate, a hydrate of strontium nitrate, a hydrate of cerium nitrate, a hydrate of copper nitrate and a hydrate of samarium nitrate;

[0018] The mass of the anhydrous aluminum nitrate or the aluminum nitrate hydrate is independently 5-40% of the mass of the aluminum source;

[0019] The mass of the non-aluminum nitrate is 0.1-10% of the mass of the aluminum source.

[0020] Preferably, the amount of the reducing agent added is 0.5 to 2 times the molar amount of the oxidant for complete reaction.

[0021] Preferably, the heat treatment temperature is 200-400°C and the insulation time is 0.1-2 h.

[0022] Preferably, the nitriding temperature is 1300-1600° C.; and the nitriding time is 2-10 h.

[0023] Preferably, the decarburization temperature is 600-800°C, and the decarburization time is 0.5-3 h.

[0024] The present invention also provides aluminum nitride powder obtained by the preparation method described in the above technical solution, wherein the aluminum nitride powder includes aluminum nitride powder with a particle size concentrated in the range of 80 to 200 nm and aluminum nitride powder with a particle size concentrated in the range of 0.7 to 3.2 μm;

[0025] The mass of the aluminum nitride powder with a particle size concentrated in the range of 80 to 200 nm accounts for 5 to 20% of the mass of the aluminum nitride powder; the mass of the aluminum nitride powder with a particle size concentrated in the range of 0.7 to 3.2 μm accounts for 80 to 95% of the mass of the aluminum nitride powder.

[0026] The present invention also provides an aluminum nitride powder obtained by the preparation method described in the above technical solution or the use of the aluminum nitride powder described in the above technical solution in preparing an aluminum nitride ceramic substrate, wherein the thermal conductivity of the aluminum nitride ceramic substrate is 120-200 W / (m·K).

[0027] The present invention provides a method for preparing an in-situ graded aluminum nitride powder, comprising the following steps: dispersing an aluminum source, a carbon source, an oxidant and a reductant in a polar solvent to obtain a precursor suspension; the oxidant is anhydrous aluminum nitrate and a non-aluminum nitrate, or a hydrate of aluminum nitrate and a non-aluminum nitrate; the reductant is urea; spray drying the precursor suspension to obtain a precursor powder; heat treating the precursor powder to cause the precursor powder to undergo a self-combustion reaction to obtain a heat-treated powder; nitriding the heat-treated powder in a nitrogen-containing atmosphere to obtain a nitrided powder; and decarburizing the nitrided powder in an oxidizing atmosphere to obtain an in-situ graded aluminum nitride powder. The present invention adds an oxidant and a reductant to the raw materials, and the self-combustion reaction products of the oxidant and the reductant can play multiple roles. For example, when the oxidant and the reductant undergo a self-combustion reaction, nitrogen and corresponding metal oxides (metal oxides corresponding to the oxidant) are generated. Nitrogen can create more gaps between raw material particles, strengthen the mass transfer between gas-phase raw materials and solid-phase raw materials, accelerate the nitriding reaction speed, and shorten the nitriding reaction time. The corresponding metal oxide particles are evenly distributed in the powder after heat treatment, and the fine particles of metal oxide generated by the combustion of the oxidant can be used as a flux to reduce the reaction temperature. Therefore, compared with the traditional carbon thermal reduction method, the present invention adopts the self-combustion-nitriding method, which has the advantages of low nitriding reaction temperature and low reaction energy consumption. At the same time, the present invention adopts spray drying to mix the raw materials. Compared with the mechanical grinding in the direct nitriding method or the carbon thermal reduction method, the raw materials are mixed more evenly and will not form agglomerations due to agglomeration, thereby improving the aluminum source conversion rate.

[0028] In addition, the oxidant of the present invention contains anhydrous aluminum nitrate, so the fine-particle aluminum oxide produced by the self-combustion of the oxidant will also be converted into aluminum nitride after nitridation. Since the aluminum nitride generated by the oxidant has a smaller particle size, the aluminum nitride generated by the nitridation reaction with the aluminum source in the raw material constitutes a distribution of aluminum nitride particles of different particle sizes, which plays an effect of in-situ powder grading. Moreover, in the subsequent aluminum nitride ceramic substrate preparation process, the small-particle aluminum nitride fills the gaps between the large-particle aluminum nitride, and the large and small particle sizes are closely stacked to form a better heat conduction path. At the same time, the small-particle particles can be used as flux to reduce the sintering temperature of the aluminum nitride ceramic substrate. DETAILED DESCRIPTION

[0029] The present invention provides a method for preparing in-situ graded aluminum nitride powder, comprising the following steps:

[0030] Dispersing an aluminum source, a carbon source, an oxidant and a reductant in a polar solvent to obtain a precursor suspension; the oxidant is anhydrous aluminum nitrate and a non-aluminum nitrate, or a hydrate of aluminum nitrate and a non-aluminum nitrate; the reductant is urea;

[0031] spray drying the precursor suspension to obtain a precursor powder;

[0032] The precursor powder is subjected to heat treatment to cause the precursor powder to undergo a self-combustion reaction to obtain a heat-treated powder;

[0033] nitriding the heat-treated powder in a nitrogen-containing atmosphere to obtain a nitrided powder;

[0034] The nitrided powder is decarburized in an oxidizing atmosphere to obtain in-situ graded aluminum nitride powder.

[0035] The invention disperses an aluminum source, a carbon source, an oxidant and a reductant in a polar solvent to obtain a precursor suspension.

[0036] As an embodiment, the aluminum source is at least one of aluminum oxide, aluminum hydroxide and boehmite; in a specific example, the aluminum source may be aluminum oxide.

[0037] As an embodiment, the carbon source is at least one of carbon black, glucose, sucrose, starch, cellulose, chitosan and chitin. In a specific embodiment, it can be carbon black and glucose.

[0038] As an embodiment, the oxidant is anhydrous aluminum nitrate and non-aluminum nitrate, or a hydrate of aluminum nitrate and a non-aluminum nitrate. As an embodiment, the non-aluminum nitrate includes at least one of yttrium nitrate, strontium nitrate, cerium nitrate, copper nitrate, samarium nitrate, a hydrate of yttrium nitrate, a hydrate of strontium nitrate, a hydrate of cerium nitrate, a hydrate of copper nitrate and a hydrate of samarium nitrate.

[0039] As an embodiment, the reducing agent is urea.

[0040] As an embodiment, the polar solvent includes water and / or ethanol. In a specific example, the polar solvent may be water.

[0041] As an embodiment, the molar ratio of the carbon element in the carbon source to the aluminum element in the aluminum source is 1.5-10:1, and in a specific embodiment, it can be 3-8:1.

[0042] As an embodiment, the mass of the anhydrous aluminum nitrate or the aluminum nitrate hydrate is independently 5-40% of the mass of the aluminum source, and in a specific embodiment, it can be 20-40%; as an embodiment, the mass of the non-aluminum nitrate is 0.1-10% of the mass of the aluminum source, and in a specific embodiment, it can be 2-9%.

[0043] As an embodiment, the amount of the reducing agent added is 0.5 to 2 times the molar amount of the oxidant for complete reaction, and in a specific embodiment, it can be 1.25 or 1.5 times.

[0044] As an embodiment, the dispersing method is ultrasonic stirring.

[0045] After obtaining the precursor suspension, the present invention spray-dries the precursor suspension to obtain precursor powder.

[0046] As an embodiment, the spray drying is carried out in a vacuum spray drying device, and the spray drying temperature is 80-120°C, and in a specific embodiment, it can be 100°C.

[0047] After the precursor powder is obtained, the present invention performs heat treatment on the precursor powder to make the precursor powder undergo a self-combustion reaction to obtain a heat-treated powder.

[0048] As an implementation mode, the heat treatment is performed in a gas atmosphere; the gas atmosphere is at least one of air, nitrogen or argon, and in a specific embodiment, it can be argon.

[0049] As an implementation mode, the temperature of the heat treatment is 200-400°C, and the holding time is 0.1-2 h. In a specific embodiment, the temperature of the heat treatment can be 300°C, and the holding time can be 2 h.

[0050] After obtaining the heat-treated powder, the present invention nitridates the heat-treated powder in a nitrogen-containing atmosphere to obtain a nitrided powder.

[0051] As an implementation mode, the nitriding temperature is 1300-1600°C, and the holding time is 2-10 h. In a specific embodiment, the nitriding temperature may be 1550°C, and the holding time may be 3 h.

[0052] After obtaining the nitrided powder, the present invention decarburizes the nitrided powder in an oxidizing atmosphere to obtain in-situ graded aluminum nitride powder.

[0053] As an embodiment, the oxidizing atmosphere is an air atmosphere.

[0054] As an implementation mode, the decarburization temperature is 600-800°C, and the decarburization time is 0.5-3 h; in a specific embodiment, the decarburization temperature can be 700°C, and the decarburization time can be 2 h.

[0055] The present invention also provides aluminum nitride powder obtained by the preparation method described in the above technical solution, wherein the aluminum nitride powder includes aluminum nitride powder with a particle size concentrated in the range of 80 to 200 nm and aluminum nitride powder with a particle size concentrated in the range of 0.7 to 3.2 μm;

[0056] The mass of the aluminum nitride powder with a particle size concentrated in the range of 80 to 200 nm accounts for 5 to 20% of the mass of the aluminum nitride powder; the mass of the aluminum nitride powder with a particle size concentrated in the range of 0.7 to 3.2 μm accounts for 80 to 95% of the mass of the aluminum nitride powder.

[0057] The present invention also provides an aluminum nitride powder obtained by the preparation method described in the above technical solution or the use of the aluminum nitride powder described in the above technical solution in preparing an aluminum nitride ceramic substrate, wherein the thermal conductivity of the aluminum nitride ceramic substrate is 120-200 W / (m·K).

[0058] The present invention simultaneously prepares two or more aluminum nitride particles with concentrated particle size distribution ranges by a partial self-combustion-nitridation method, and aluminum nitride particles of different particle sizes are evenly distributed, achieving the effect of in-situ powder grading. Compared with the traditional carbon thermal reduction method, the preparation method has the advantages of low reaction temperature, short reaction time, low reaction energy consumption, etc. When the in-situ graded aluminum nitride powder synthesized by the preparation method is used for sintering to prepare an aluminum nitride substrate, the gaps between the aluminum nitride particles can be significantly reduced, and the aluminum nitride particles can be closely stacked. After sintering, a smoother heat conduction path can be formed, and the aluminum nitride substrate prepared using the powder has better density and thermal conductivity.

[0059] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0060] Example 1

[0061] 100 g of aluminum oxide, 30 g of carbon black, 20 g of glucose, 30 g of anhydrous aluminum nitrate, 4 g of yttrium nitrate, 2 g of strontium nitrate, and urea (the amount of urea added is 1.25 times the molar amount of anhydrous aluminum nitrate, yttrium nitrate and strontium nitrate for complete reaction) are added into water and ultrasonically stirred for 2 h to form a uniformly dispersed precursor suspension; then the precursor suspension is spray dried in a vacuum spray drying equipment (temperature is 100 °C) to obtain a uniform precursor powder;

[0062] The precursor powder was heat treated at 300 °C for 2 h in an argon atmosphere to produce a self-combustion reaction, and then the heat-treated powder was treated at 1550 °C for 3 h in a nitrogen atmosphere for nitridation. Finally, the nitrided powder was treated at 700 °C for 2 h in an air atmosphere for decarburization to obtain in-situ graded aluminum nitride powder.

[0063] The particle size distribution of the in-situ graded aluminum nitride powder in this embodiment is that the particle size is concentrated around 140 nm with a mass fraction of 6.5%, and the particle size is concentrated around 1.4 μm with a mass fraction of 93.5%.

[0064] Example 2

[0065] 100 g of aluminum oxide, 30 g of carbon black, 30 g of glucose, 50 g of anhydrous aluminum nitrate, 4 g of yttrium nitrate, 2 g of strontium nitrate, and urea (the amount of urea added is 1.25 times the molar amount of the complete reaction of anhydrous aluminum nitrate, yttrium nitrate and strontium nitrate) are added to water and ultrasonically stirred for 2 h to form a uniformly dispersed precursor suspension; then the precursor suspension is spray dried in a vacuum spray drying equipment (temperature is 100 °C) to obtain a uniform precursor powder;

[0066] The precursor powder was heat treated at 300 °C for 2 h in an argon atmosphere to produce a self-combustion reaction. The powder after the self-combustion reaction was then treated at 1550 °C for 3 h in a nitrogen atmosphere for nitridation. Finally, the nitrided powder was treated at 700 °C for 2 h in an air atmosphere for decarburization to obtain in-situ graded aluminum nitride powder.

[0067] The particle size distribution of the in-situ graded aluminum nitride powder in this embodiment is that the particle size is concentrated around 140 nm with a mass fraction of 10%, and the particle size is concentrated around 1.4 μm with a mass fraction of 90%.

[0068] Example 3

[0069] 100 g of aluminum oxide, 30 g of carbon black, 30 g of glucose, 50 g of anhydrous aluminum nitrate, 2 g of yttrium nitrate, 4 g of strontium nitrate, and urea (the amount of urea added is 1.25 times the molar amount of the complete reaction of anhydrous aluminum nitrate, yttrium nitrate and strontium nitrate) are added to water and ultrasonically stirred for 2 h to form a uniformly dispersed precursor suspension; then the precursor suspension is spray dried in a vacuum spray drying equipment (temperature is 100 °C) to obtain a uniform precursor powder;

[0070] The precursor powder was heat treated at 300 °C for 2 h in an argon atmosphere to produce a self-combustion reaction. The powder after the self-combustion reaction was then treated at 1550 °C for 3 h in a nitrogen atmosphere for nitridation. Finally, the nitrided powder was treated at 700 °C for 2 h in an air atmosphere for decarburization to obtain in-situ graded aluminum nitride powder.

[0071] The particle size distribution of the in-situ graded aluminum nitride powder in this embodiment is that the particle size is concentrated around 140 nm with a mass fraction of 10%, and the particle size is concentrated around 1.4 μm with a mass fraction of 90%.

[0072] Example 4

[0073] 100 g of aluminum oxide, 30 g of carbon black, 30 g of glucose, 70 g of anhydrous aluminum nitrate, 4 g of yttrium nitrate, 2 g of strontium nitrate, and urea (the amount of urea added is 1.25 times the molar amount of the complete reaction of anhydrous aluminum nitrate, yttrium nitrate and strontium nitrate) are added to water and ultrasonically stirred for 2 h to form a uniformly dispersed precursor suspension; then the precursor suspension is spray dried in a vacuum spray drying equipment (temperature is 100 °C) to obtain a uniform precursor powder;

[0074] The precursor powder was heat treated at 300 °C for 2 h in an argon atmosphere to produce a self-combustion reaction. The powder after the self-combustion reaction was then treated at 1550 °C for 3 h in a nitrogen atmosphere for nitridation. Finally, the nitrided powder was treated at 700 °C for 2 h in an air atmosphere for decarburization to obtain in-situ graded aluminum nitride powder.

[0075] The particle size distribution of the in-situ graded aluminum nitride powder in this embodiment is that the particle size is concentrated around 140 nm with a mass fraction of 14%, and the particle size is concentrated around 1.4 μm with a mass fraction of 86%.

[0076] Example 5

[0077] 100 g of aluminum oxide, 30 g of carbon black, 30 g of glucose, 50 g of anhydrous aluminum nitrate, 6 g of yttrium nitrate, 4 g of strontium nitrate, and urea (the amount of urea added is 1.5 times the molar amount of anhydrous aluminum nitrate, yttrium nitrate and strontium nitrate for complete reaction) are added into water and ultrasonically stirred for 2 h to form a uniformly dispersed precursor suspension; the precursor suspension is then spray dried (temperature is 100 °C) to obtain a uniform precursor powder;

[0078] The precursor powder was heat treated at 300 °C for 2 h in an argon atmosphere to produce a self-combustion reaction. The powder after the self-combustion reaction was then treated at 1550 °C for 3 h in a nitrogen atmosphere for nitridation. Finally, the nitrided powder was treated at 700 °C for 2 h in an air atmosphere for decarburization to obtain in-situ graded aluminum nitride powder.

[0079] The particle size distribution of the in-situ graded aluminum nitride powder in this embodiment is that the particle size is concentrated around 140 nm with a mass fraction of 10%, and the particle size is concentrated around 1.4 μm with a mass fraction of 90%.

[0080] Application Example 1

[0081] The aluminum nitride powder prepared in Example 1 was sintered at 1750° C. for 2 hours under normal pressure to obtain an aluminum nitride ceramic substrate.

[0082] Application Example 2

[0083] The only difference from Application Example 1 is that the aluminum nitride powder prepared in Example 1 is replaced by the aluminum nitride powder prepared in Example 2.

[0084] Application Example 3

[0085] The only difference from Application Example 1 is that the aluminum nitride powder prepared in Example 1 is replaced by the aluminum nitride powder prepared in Example 3.

[0086] Application Example 4

[0087] The only difference from Application Example 1 is that the aluminum nitride powder prepared in Example 1 is replaced by the aluminum nitride powder prepared in Example 4.

[0088] Application Example 5

[0089] The only difference from Application Example 1 is that the aluminum nitride powder prepared in Example 1 is replaced by the aluminum nitride powder prepared in Example 5.

[0090] The density and thermal conductivity of the aluminum nitride ceramic substrates obtained in application examples 1 to 5 were tested, and the test results are shown in Table 1.

[0091] The density is measured using the Archimedean drainage method. First, the residual powder and other impurities on the sample surface are removed by grinding. Using a density balance, the mass of the sample in the air is recorded as m1. Then the sample is immersed in water, and the mass of the sample in water is recorded as m2. The density ρ is calculated using the following formula:

[0092] ρ=ρ 水 ·m1 / (m1- m2).

[0093] Thermal conductivity The thermal diffusion coefficient α of the sample was measured using a laser thermal conductivity analyzer, and the thermal conductivity λ was calculated according to the following formula:

[0094] λ = αρC p

[0095] Where ρ is the sample density; C p is the heat capacity of the sample, and the heat capacity of aluminum nitride is 0.734 J / (g·K).

[0096] Table 1 Density and thermal conductivity of aluminum nitride ceramic substrates obtained in application examples 1 to 5

[0097]

[0098] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing in-situ graded aluminum nitride powder, characterized in that: The following steps are involved: dispersing an aluminum source, a carbon source, an oxidant and a reductant in a polar solvent to obtain a precursor suspension; The aluminum source is at least one of aluminum oxide, aluminum hydroxide and boehmite; the oxidant is anhydrous aluminum nitrate and non-aluminum nitrate, or a hydrate of aluminum nitrate and a non-aluminum nitrate; the reducing agent is urea; the molar ratio of the carbon element in the carbon source to the aluminum element in the aluminum source is 1.5-10:1; the mass of the anhydrous aluminum nitrate or the hydrate of aluminum nitrate in the oxidant is independently 5-40% of the mass of the aluminum source; the mass of the non-aluminum nitrate is 0.1-10% of the mass of the aluminum source; the amount of the reducing agent added is 0.5-2 times the molar amount of the oxidant for complete reaction; spray drying the precursor suspension to obtain a precursor powder; The precursor powder is subjected to heat treatment to cause the precursor powder to undergo a self-combustion reaction to obtain a heat-treated powder; In a nitrogen-containing atmosphere, nitriding the heat-treated powder to obtain a nitrided powder; Decarburizing the nitrided powder in an oxidizing atmosphere to obtain in-situ graded aluminum nitride powder; The aluminum nitride powder includes aluminum nitride powder with a particle size concentrated in 80~200nm and aluminum nitride powder with a particle size concentrated in 0.7~3.2μm; the mass of the aluminum nitride powder with a particle size concentrated in 80~200nm is 5~20% of the mass of the aluminum nitride powder; the mass of the aluminum nitride powder with a particle size concentrated in 0.7~3.2μm is 80~95% of the mass of the aluminum nitride powder.

2. The preparation method according to claim 1, characterized in that The polar solvent includes water and / or ethanol.

3. The preparation method according to claim 1, characterized in that: The carbon source is at least one of carbon black, glucose, sucrose, starch, cellulose, chitosan and chitin.

4. The preparation method according to claim 1, characterized in that: The non-aluminum nitrate includes at least one of yttrium nitrate, strontium nitrate, cerium nitrate, copper nitrate, samarium nitrate, a hydrate of yttrium nitrate, a hydrate of strontium nitrate, a hydrate of cerium nitrate, a hydrate of copper nitrate, and a hydrate of samarium nitrate.

5. The preparation method according to claim 1, characterized in that: The heat treatment temperature is 200-400° C. and the heat preservation time is 0.1-2 hours.

6. The preparation method according to claim 1, characterized in that: The decarburization temperature is 600-800°C, and the decarburization time is 0.5-3h.

7. The preparation method according to claim 1, characterized in that: The nitriding temperature is 1300-1600° C.; the nitriding time is 2-10 hours.

8. The aluminum nitride powder obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The aluminum nitride powder includes aluminum nitride powder with a particle size concentrated in the range of 80 to 200 nm and aluminum nitride powder with a particle size concentrated in the range of 0.7 to 3.2 μm; The mass of the aluminum nitride powder with a particle size concentrated in the range of 80-200 nm accounts for 5-20% of the mass of the aluminum nitride powder; the mass of the aluminum nitride powder with a particle size concentrated in the range of 0.7-3.2 μm accounts for 80-95% of the mass of the aluminum nitride powder.

9. Use of the aluminum nitride powder obtained by the preparation method according to any one of claims 1 to 7 or the aluminum nitride powder according to claim 8 in an aluminum nitride ceramic substrate, characterized in that: The thermal conductivity of the aluminum nitride ceramic substrate is 120-200 W / (m·K).

Citation Information

Patent Citations

  • Method for preparing aluminium nitride powder

    CN1435371A